2009
DOI: 10.1007/s00268-009-0172-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Rebleeding and Death in Alcoholic Cirrhotic Patients with Acute Variceal Bleeding: A Multivariate Analysis

Abstract: Survival was influenced by the severity of liver failure, with most deaths occurring in Child-Pugh grade C patients. Patients with AVH and encephalopathy, ascites, bilirubin levels >51 mmol/l, INR >2.3, albumin <25 g/l and who require balloon tube tamponade are at increased risk of dying within the first 6 weeks. Bilirubin levels >51 mmol/l and transfusion of >6 units of blood were predictors of variceal rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 72 publications
4
28
1
5
Order By: Relevance
“…Early rebleeding and mortality rate increase sharply within 6 weeks period then stabilized. Early rebleeding rate in the current study was 25.5%, a similar result reported by Krige et al [12] but it is slightly higher than that in some other studies [3] [13] while it is lower than that in other studies [14] [15].…”
Section: Discussionsupporting
confidence: 35%
“…Early rebleeding and mortality rate increase sharply within 6 weeks period then stabilized. Early rebleeding rate in the current study was 25.5%, a similar result reported by Krige et al [12] but it is slightly higher than that in some other studies [3] [13] while it is lower than that in other studies [14] [15].…”
Section: Discussionsupporting
confidence: 35%
“…Table (5) compares the studied groups as regards rate and causes of rebleeding and mortality rate and shows that there were no significant differences between them. Correlation between the rate of rebleeding and study parameters revealed that the rate of rebleeding has significant positive correlation with Child's score, PT, INR, grade of OV, presence of risky signs, number of units of blood transfused during resuscitation, amount of sclerosing agent and number of rubber bands used as shown in table (6). …”
Section: Resultsmentioning
confidence: 99%
“…The risk of rebleeding is greatest during the first few days after initial variceal hemorrhage [5]. Survival after variceal bleeding depends largely on the rapidity and efficacy of initial primary hemostasis and the presence and severity of underlying liver disease and hepatic functional reserve [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'hémostase primaire dans les deux groupes de patients (ulcères hémorragiques et ruptures des varices oesogastriques) était similaire aux résultats rapportés dans la littérature [36][37][38].…”
Section: Discussionunclassified